2019
DOI: 10.1002/npr2.12058
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in AMPA receptor subunit expression and receptor binding among patients with addictive disorders: A systematic review of human postmortem studies

Abstract: Background and Objectives Altered trafficking of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptors has been reported in postmortem studies and suggested the involvement of AMPA receptors in the pathophysiology underpinning addictive disorders. However, these findings seemed mixed. Methods A systematic literature search was conducted, using PubMed and Embase (last search, August 2018), to identify human postmortem studies that examined the expression of proteins and mRNA of AMPA receptor sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…AMPA receptors are a subtype of ionotropic glutamate receptors that are vital for fast synaptic neurotransmission and long‐term potentiation (LTP) within the central nervous system and have recently been under investigation for their role in modulating alcohol consumption (Corbit et al, 2014; Dannenhoffer and Spear, 2019; Henley and Wilkinson, 2016; Ruda‐Kucerova et al, 2018; Ueno et al, 2019; Wang et al, 2012). LTP is dependent on the insertion of AMPA receptors into the postsynaptic membrane where glutamate binding to AMPA receptors is necessary to cause postsynaptic depolarization of the membrane ultimately leading to an up‐regulation of LTP‐dependent AMPA receptors.…”
mentioning
confidence: 99%
“…AMPA receptors are a subtype of ionotropic glutamate receptors that are vital for fast synaptic neurotransmission and long‐term potentiation (LTP) within the central nervous system and have recently been under investigation for their role in modulating alcohol consumption (Corbit et al, 2014; Dannenhoffer and Spear, 2019; Henley and Wilkinson, 2016; Ruda‐Kucerova et al, 2018; Ueno et al, 2019; Wang et al, 2012). LTP is dependent on the insertion of AMPA receptors into the postsynaptic membrane where glutamate binding to AMPA receptors is necessary to cause postsynaptic depolarization of the membrane ultimately leading to an up‐regulation of LTP‐dependent AMPA receptors.…”
mentioning
confidence: 99%
“…There have been post-mortem brain studies that measure AMPARs in the brain. According to systematic literature reviews, there are differences in AMPAR subunit expression and receptor binding in the postmortem brain between patients with psychiatric conditions, including schizophrenia, depression, and addictive disorders, and healthy controls 68 ) (Uchida et al and Koizumi et al , in preparation for publication); however, the findings regarding their relative quantity in comparison to healthy controls and the affected regions were inconsistent across the studies. Degrading changes after death and the activity-dependent nature of AMPARs render human postmortem studies challenging.…”
Section: Imminent Need To Elucidate the Pathophysiology Of Psychiatrimentioning
confidence: 99%
“…Degrading changes after death and the activity-dependent nature of AMPARs render human postmortem studies challenging. 68 ) Moreover, subjects included in these post-mortem studies were not comprehensively characterized in terms of their diagnosis and illness severity. Such a stagnating situation clearly highlighted the necessity for examining AMPARs in the living brain of well-characterized patients with psychiatric disorders in the real-world.…”
Section: Imminent Need To Elucidate the Pathophysiology Of Psychiatrimentioning
confidence: 99%
“…There seems to be a particular yet inconclusively described role of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in the human substance abusers pointing to a single relatively consistent outcome -an increase in the hippocampal expression of AMPA receptor subunits (Ueno et al, 2019). In preclinical research, multiple drugs were shown to exert alterations of AMPA receptor subunits' expression in reward-related brain areas, typically nucleus accumbens or ventral tegmental area, e.g., cocaine (Sutton et al, 2003), amphetamine (Cruz et al, 2008), nicotine (Wang et al, 2007) or methamphetamine (Scheyer et al, 2016;Murray et al, 2019).…”
Section: Introductionmentioning
confidence: 99%